Investigation of the reactivity of 5,6-dihydrothymidin-5-yl and its involvement in DNA damage amplification - Tallman, Keri Ann, author; Greenberg, Mark M., advisor (Colorado State University. Libraries, 2000)
The reactivity of 5,6-dihydrothymidin-5-yl (4 and 120) was investigated at the monomeric level and in a dinucieotide using the phenyl selenide (96 and 121) as the thermal and photochemical precursor. By studying the reactivity of 4 (and 120) at the monomeric level and in a dinucleotide, insight into the mechanism by which 5.6-dihydrothymidin-5-yl is involved in DNA damage amplification was attained. The nucleobase radical (4 and 120) was studied in the absence and presence of O2, as well as in the presence of radiosensitizers. By using anomerization and tetranitromethane as mechanistic probes, we have shown that 120 does not participate in internucleotidyl hydrogen atom abstraction, but is reduced to form the nonmutagenic lesion, 5,6-dihydrothymidine (128). The generation of the radical (4) in the presence of O2 resulted in the formation of the peroxyl radical (7), which we have shown undergoes superoxide (O2-∙) elimination to restore the native nucleobase, thymidine (3). Evidence for this mechanism was attained by spectrophotometric assays involving the oxidation of epinephrine and reduction of cytochrome c for the detection of O2-∙. Competitive kinetics was used to estimate the rate constant for O2-∙ elimination as 21 s-1. Direct evidence for internucleotidyl hydrogen atom abstraction by the peroxyl radical (163) was gained by the formation of the 2-deoxyribonolactone lesion (132), which occurs preferentially from 5S-163. The transfer of spin from the nucleobase to the sugar occurs in competition with O2-∙ elimination and intermolecular hydrogen atom abstraction with a rate constant of 0.1 s-1. 5,6-Dihydrothymidin-5-yl (4 and 120) also reacts with the metabolite of tirapazamine (11), the I-N-oxide (12), and results in the formation of 2-deoxyribonolactone (132). The mechanism by which the nucleobase radical is trapped by 12 is unclear, but evidence suggests that regioisomeric trapping of the radical (4 and 120) on the nitrogen and oxygen occurs to form a mixture of covalent adducts. Although the nature of the reactive species responsible for internucleotidyl hydrogen atom abstraction is unknown, it is clear that the I-N-oxide (12) can serve as a surrogate for O2 and produce tandem lesions.
Keywords: organic chemistry